Biological activity of cinnamon and cardamom oils on some virulence factors of Pseudomonas aeruginosa - Shaimaa Ghazi Younis Mohammed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Drug-resistant Pseudomonas aeruginosa poses a severe global health hazard, demanding alternative therapeutic strategies. Specific Background: Plant-derived essential oils such as cinnamon and cardamom oils are investigated for their potential to target bacterial virulence factors without triggering antimicrobial resistance. Knowledge Gap: However, the comparative efficacy of cinnamon oil versus cardamom oil in suppressing biofilm development, pigment production, and bacterial motility remains insufficiently characterized. Aims: This study evaluated the comparative biological activity of cinnamon and cardamom oils against biofilm formation, pyocyanin production, and swarming motility in a clinical isolate of P. aeruginosa. Results: Microtiter plate assays revealed that cinnamon oil successfully reduced strong biofilm formation to weak biofilm formation at 0.8 µl/ml and suppressed pyocyanin production at 0.4–0.8 µl/ml, while significantly restricting swarming motility; conversely, cardamom oil showed no effect on biofilm formation at any tested concentration and exhibited lower efficacy in inhibiting pigment production and movement. Novelty: This study demonstrates the superior, concentration-dependent anti-virulence potency of cinnamon oil over cardamom oil against P. aeruginosa. Implications: These findings support the potential application of cinnamon oil as a natural therapeutic agent to attenuate key virulence factors in multidrug-resistant Keywords : Cinnamon Oil, Cardamom Oil, Pseudomonas Aeruginosa, Biofilm Formation, Pyocyanin Production Key Findings Highlights Cinnamon oil effectively converted strong biofilm production to weak biofilm production at 0.8 µl/ml, whereas cardamom oil exhibited no anti-biofilm activity at any tested concentration. Pyocyanin pigment synthesis was fully suppressed by cinnamon oil at concentrations between 0.4 and 0.8 µl/ml, demonstrating significantly higher inhibitory activity than cardamom oil. Swarming motility on agar was markedly restricted by cinnamon oil compared to cardamom oil and untreated controls.